Русский тоталитарный язык в воспроизведении Андрея Платонова (повесть "Котлован") - КУПИНА, НАТАЛИЯ А. (Stylistyka, 2021)
The author shows meaniigful specific character of the tota1itarian linguistic image in the antiutopian story Foundation area (Kotlovan). Оп the background of ideological dominating idea of the text the system of speech gеше reproduced bу the writer is described. Besides the preva1ing type of speech behaviour becomes evident. Peculiarities of ideo1ogica1 concepts of action, aim, destination are a1so characterized there.